2020
DOI: 10.1108/jcp-03-2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

Classification of malicious insiders and the association of the forms of attacks

Abstract: Purpose The authors argue that the current studies about malicious insiders confuse the fact that malicious attacks belong to two different categories, namely, those that launch instrumental attacks and expressive attacks. The authors collect malicious insider data from publicly available sources and use text-mining techniques to analyze the association between malicious insiders’ characteristics and the different types of attack. Design/methodology/approach The authors investigated the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…Caucasian, African-American, Asian) and gender (males vs females). A psychological research study (Glancy et al , 2020) used a text mining approach to identify the links between malicious insiders’ behaviour and the different types of attacks. The study found that malicious insiders who were arrogant in behaviour tended to conduct dramatic attacks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Caucasian, African-American, Asian) and gender (males vs females). A psychological research study (Glancy et al , 2020) used a text mining approach to identify the links between malicious insiders’ behaviour and the different types of attacks. The study found that malicious insiders who were arrogant in behaviour tended to conduct dramatic attacks.…”
Section: Literature Reviewmentioning
confidence: 99%